THE INFLUENCE OF WORK DISCIPLINE AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT THE STARTUP COMPANY SI CEPAT - Felix Lim; Stefanus William Wongkar; Dede Ansyari Guci; Puspa Liza Ghazali; Efendy Salim (Mount Hope Economic Global Journal, 2024)
Si Cepat is a startup company specializing in logistics and delivery services. The company faces issues with declining employee performance, low work discipline, and incomplete implementation of situational leadership. This study aims to examine the impact of Work Discipline and Leadership Style on Employee Performance at Si Cepat. The research uses a quantitative approach with an associative method. The population consists of 361 employees, with a sample of 190 employees. The model applied is multiple linear regression. The results indicate that Work Discipline and Leadership Style have an impact on Employee Performance at Si Cepat.